2001
DOI: 10.1002/1521-3765(20010417)7:8<1734::aid-chem17340>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

The Photohydration ofN-Alkylpyridinium Salts: Theory and Experiment

Abstract: Bicyclic aziridines formed by the irradiation of pyridinium salts in basic solution have recently been recognized to have great synthetic potential. We have undertaken a joint computational and experimental investigation of the mechanism of this photoreaction. We have computationally determined the structures and relative energies of the relevant stationary points on the lowest potential energy surface (PES) of the pyridinium and methylpyridinium ions. Two important intermediates are shown to be bound minima o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“… 78 We now confirm this feature for silabenzene at the CASPT2//CASSCF level ( Figure 5 ), and also for the pyridinium cation, which has a photochemistry which is of higher synthetic value than that of pyrazine. 79 84 Yet, at the lower CASSCF level, which contains only static electron correlation, there are still activation barriers, although they are smaller than for S 1 -state benzene. Thus, the activation barrier observed in the S 1 state of benzene is traceable to its high symmetry (for comparisons between the S 1 states of benzene, silabenzene, and pyridinium ion, see Table S19 ).…”
Section: Results and Discussionmentioning
confidence: 96%
“… 78 We now confirm this feature for silabenzene at the CASPT2//CASSCF level ( Figure 5 ), and also for the pyridinium cation, which has a photochemistry which is of higher synthetic value than that of pyrazine. 79 84 Yet, at the lower CASSCF level, which contains only static electron correlation, there are still activation barriers, although they are smaller than for S 1 -state benzene. Thus, the activation barrier observed in the S 1 state of benzene is traceable to its high symmetry (for comparisons between the S 1 states of benzene, silabenzene, and pyridinium ion, see Table S19 ).…”
Section: Results and Discussionmentioning
confidence: 96%
“…In the original reports describing the photochemistry of pyrylium and pyridinium salts, the assumption was made that the heteroatom containing benzvalene cations 42 serve as initially formed intermediates and/or as intermediates in ring rearrangement pathways. The results of more recent theoretical studies 23 show that tricyclic cations (42, X = NR) derived from pyridinium salts have a higher energy content than the corresponding bicyclicaziridine cations (43, X = NR). Thus, it appears that neighboring group stabilization of the allylic cation in 43 (X = NR) by nitrogen is prevented by increased ring strain associated with formation of the tricyclic framework.…”
Section: Methodsmentioning
confidence: 99%
“…In 2001, prompted by the renaissance of the synthetic photochemistry of pyridinium salts, Burger and L üthi et al reported their insights into the events originating from p → p* excitation. 18 Completely optimised geometries for the equilibrium, intermediate and transition state structures of species arising from pyridinium and methyl pyridinium ions were determined using a combination of restricted Hartree-Fock (RHF) and density functional theory DFT (B3LYP) calculations (Fig. 1).…”
Section: Theoretical and Mechanistic Studies Of Burger And Co-workersmentioning
confidence: 99%